Association between egoistic motivation and participation in sports volunteering among college students: the moderating effect of social norms and perceived organizational support - Zhang, Dawei; Wang, Junying; Tian, Shengguo; Liu, Li; Zhang, Xiao (Frontiers in Psychology, 2025)
IntroductionThis study employs motivation theory as its primary analytical framework to examine the relationship between egoistic motivation and college students' participation in sports volunteer services, along with its underlying mechanisms. The research aims to provide a novel explanatory framework for understanding how egoistic motivation transforms into altruistic behavior and to offer practical implications for mobilizing college students' potential in sports volunteering.MethodsA structured questionnaire survey was conducted among 684 students (424 males and 260 females, aged 16–28) from six leading sports universities in China, including Shanghai University of Sport and Beijing Sport University. Data analysis was performed using STATA 16.0, utilizing logistic regression supplemented by tests of interaction and higher-order moderation effects to examine the roles of social norms and perceived organizational support.ResultsThe results revealed three key findings: (1) egoistic motivation had a significant positive effect on students' participation in sports volunteer service; (2) social norms significantly moderated the relationship between egoistic motivation and participation behavior; and (3) perceived organizational support further strengthened the moderating effect of social norms, demonstrating a significant higher-order moderation effect.DiscussionThese findings provide new insights into the psychological mechanisms underlying the transformation from egoistic motivation to altruistic behavior. The study contributes to the development of more effective public fitness service systems by offering evidence-based approaches to enhance college students' engagement in sports volunteering activities.